PENGELOLAAN LINGKUNGAN DENGAN CARA MEMANFAATKAN FLY ASH BATUBARA SEBAGAI BAHAN BAKU MEMBRAN SILIKA DALAM UPAYA MEMINIMALISIR LIMBAH B3 DI PT SEMEN BATURAJA OKU - Lety Trisnaliani; Indah Purnamasari; Ahmad Zikri; Selastia Yuliati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2018)
The target of community service assignments in 2018 is productive communities that need development in the field of environmental management, namely employees of the Quality Control Laboratory of PT. Semen Baturaja OKU. Coal ash is a waste unlike gas from combustion, because it is a solid material that is not easily dissolved and is not volatile so it will be more troublesome in handling. If the amount is large and is not handled properly, then the coal ash can pollute the environment especially caused by fly ash and can be sucked by humans and animals can also affect the condition of the surrounding water and soil so that it can kill the plants. The chemical composition of Fly ash is silica, alumina and iron with little calcium, magnesium, sulfate, and other components. Currently coal fly ash is used in cement plants as a mixture of concrete makers. Because of the smoothness and round shape of the granules, the use of fly ash on the concrete mixture can increase the slack on the concrete mixture. The advantages of using fly ash include increasing the strength of concrete, filling the pores in the concrete so that the porosity of the concrete becomes low, while increasing the density of concrete so that it can increase the tightness of concrete to water. The coal fly ash waste that accumulates also occurs in the industry of PT Semen Baturaja Ogan Komering Ulu. PT. Semen Baturaja is one of the largest cement industries in Sumatra that produces PCC (Portland Composite Cement). PCC type cement is cement made by utilizing inorganic additives such as fly ash and trass. Aside from being an additional material for cement, fly ash can also be used as a raw material for making silica membranes which serves to reduce metal content in acid mine drainage. So that the author wishes to socialize the employees and employees of PT Semen Baturaja especially in the BTA II Quality Control laboratory division to disseminate knowledge about the benefits of coal fly ash as raw material for silica membranes in minimizing B3 waste so that environmental management with a friendly environment will achieved.